Answer:
9 is the constant that should be added to make the expression perfect square.
Step-by-step explanation:
The given expression is (x² - 6x)
We have to make this expression perfect square.
As we know the formula (a-b)² = a² + b² - 2ab
Now we will rewrite the expression given in the form of the formula.
[(x)² - 2 (3)x]
We find a as x' and b as 3
So by putting a = x and b = 3 in the formula we get
(x-3)² = x² + 3² -2(x)(3)
Therefore, 9 is the constant that should be added to make the expression perfect square.